Functional Rhinoplasty. (23rd August 2013) - Jordan, James R.; Cilento, Benjamin W.; Barrera, Jose E.; Pribitkin, Edmund A.
Abstract : Program Description: Functional rhinoplasty techniques are intended to improve the nasal airway and are used in patients with more complex nasal deformities that may not be corrected with more standard techniques. This panel will address deformities of the nasal septum, internal valve, and nasal vault, along with techniques to correct these deformities. Educational Objectives: 1) Describe the various components of anatomic nasal obstruction. 2) Develop strategies to approach complex nasal deformities. 3) Implement surgical techniques to correct more complex nasal deformities.